Vietnam Power Sector : Generation Options - World Bank (Washington, DC, 2013)
This report discusses the energy sector in Vietnam. The central task for the energy sector is to meet demands for electricity in sufficient quantity and of an acceptable quality, in as commercially and financially efficient a way as possible. Several issues arise if this task is to be accomplished in the short and medium term. They are: optimizing power investments; financing the investments that must be made; implementing the reforms in the power industry and restructuring EVN; improving access and service quality; and addressing shortcomings in pricing and tariffs. This study discusses the first of these issues, though inevitably there is some overlap. The study has four specific objectives: (1) to inform decisions about technology choices; (2) to inform decisions on energy and energy sector policy; (3) to inform the energy sector planning process; and (4) to inform the internal discussion within the Bank on how Vietnam's energy sector development can be assisted.